Investigating the Linkages between FASD, Gangs, Sexual Exploitation and Woman Abuse in the Canadian Aboriginal Population: A Preliminary Study - Totten, Mark (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2010)
The purpose of this study, prepared for the Native Women’s Association of Canada (NWAC) and funded by Health Canada First Nations and Inuit Health Branch, is to provide an exploratory investigation into the linkages and to begin a journey into making the connection between FASD, sexual exploitation, gangs, and extreme violence in the lives of young Aboriginal women. Emerging data from Aboriginal gang intervention and exit projects in Canada suggest that many women experience sexual slavery and extreme violence in gangs, and that a disproportionate number also suffer from Fetal Alcohol Spectrum Disorder. Although much more research is required, preliminary data point to the importance of developing prevention strategies targeted at addressing family violence, drug and alcohol abuse, poverty, the social determinants of health and the history of colonization of Aboriginal Peoples. This work should focus on the strength and resiliency of Aboriginal peoples.